2007
DOI: 10.1080/10731190701586269
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxygen Delivery to Primary Hepatocytes within a Hollow Fiber Bioreactor Facilitated via Hemoglobin-Based Oxygen Carriers

Abstract: The production of a fully functional bioartificial liver assist device (BLAD) would greatly enhance available treatment options for patients suffering from acute liver failure. Currently, inadequate oxygen provision to hepatocytes seeded within hollow fiber bioreactors hampers development of a viable hollow fiber-based BLAD. Experimentally, oxygen provision to primary rat hepatocytes cultured within hollow fiber bioreactors was measured, it was observed that supplementation with an oxygen carrier (bovine red b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
0
36
1
Order By: Relevance
“…The transport of O 2 is then limited by the O 2 demand of the hepatoma cells, thus, the O 2 flux cannot infinitely increase but instead reaches a plateau at a relatively higher pO 2,in . Previous studies on O 2 transport in HF bioreactors showed that supplementation of hemoglobin-based oxygen carriers (HBOCs) in the cell culture media greatly enhanced O 2 transport through the HF membrane (Sullivan and Palmer, 2006;Sullivan et al, 2007). For HBOCs with varying O 2 affinity, the O 2 flux rises sharply with increasing pO 2,in and reaches a plateau at pO 2,in ¼ $60 mm Hg in a HF with the same dimensions and hepatocyte cell density used in this work (Chen and Palmer, 2009).…”
Section: Influence Of Inlet Po 2 On O 2 Fluxmentioning
confidence: 91%
“…The transport of O 2 is then limited by the O 2 demand of the hepatoma cells, thus, the O 2 flux cannot infinitely increase but instead reaches a plateau at a relatively higher pO 2,in . Previous studies on O 2 transport in HF bioreactors showed that supplementation of hemoglobin-based oxygen carriers (HBOCs) in the cell culture media greatly enhanced O 2 transport through the HF membrane (Sullivan and Palmer, 2006;Sullivan et al, 2007). For HBOCs with varying O 2 affinity, the O 2 flux rises sharply with increasing pO 2,in and reaches a plateau at pO 2,in ¼ $60 mm Hg in a HF with the same dimensions and hepatocyte cell density used in this work (Chen and Palmer, 2009).…”
Section: Influence Of Inlet Po 2 On O 2 Fluxmentioning
confidence: 91%
“…This has been demonstrated by extensive simulation work conducted in our lab. [19][20][21][22] Recent experimental studies also showed that supplementation of bovine red blood cells (bRBCs) into the circulating cell culture medium improved O 2 transport to cultured C3A cells in a HF bioreactor. 23,24 In the presence of bRBCs, the molar ratio of lactate production to glucose consumption of hepatoma cells was remarkably reduced, while albumin synthesis increased substantially, which indicates highly efficient cellular metabolism and synthetic function.…”
mentioning
confidence: 99%
“…In designing a HF-BAL, three main constraints exist on the system: (i) the cartridge must contain a cell loading of 10-40% of the liver's mass (Sullivan et al, 2007) or approximately to 10-40 billion cells for an average adult; (ii) the hollow fibers must supply the cells with adequate nutrition: oxygen is generally considered to be the main limiting nutrient in hollow fiber bioreactor (HFBR) applications (Piret and Cooney 1991); (iii) the device is limited in the range of blood/plasma flow rates that can be supplied; this is generally between 100 and 300 mL/min due to technical and rheological constraints (Pless and Sauer 2005).…”
Section: Introductionmentioning
confidence: 99%